Optimal design selection and analysis of single sided linear induction motor - Issac, Sijitha; Poorani, S (International Journal of Engineering and Technology, 2018)
This paper investigates the design and implementation of single-sided linear induction motor towards determining the end effect intensity, reduces the primary weight of the system and improves the efficiency by multi-objective optimisation approach. This optimisation technique is a combination of genetic with cuckoo search (GCS) algorithm is introduced to improvise the efficiency and power factor, as well as to minimize the end effect intensity, simultaneously. The performance of the designed novel approach will be validated based on the measure of different parameters such as Efficiency, Power factor, Maximum thrust slip, Aluminum thickness, Primary width/pole pitch, Primary current density and the braking force due to the end effect. Finally, to validate the optimisation results, 3D finite element method is employed and compared the results with the existing technique like GA, PSO, and Cuckoo search.Â